The Kingdom Saudi Arabia and the challenge of 21st century - Craze, Joshua; Huband, Mark (Columbia University Press, 2009)
A selection of writings on contemporary Saudi Arabia. It is divided into four sections, dealing respectively with Saudi domestic political issues, the Kingdom's role in regional affairs, studies of Saudi society, and cultural and religious life in the Kingdom